The Obama years : the power of words [videorecording (DVD)] - Schiliro, Jody; Williams, Jesse, 1981- (PBS Distribution, 2018)
Barack Obama launched into national consciousness at the 2004 Democratic National Convention and ever since, he's delivered messages of patriotism, unity, and hope through the power of words. Interviews with eminent historians and key figures in his writing process give rare insights into these iconic speeches, as well as the Obama presidency and the man himself.